“Clicks & Tweets” in Continuing Professional Development (CPD)? – A Cross-Cultural Comparison of ICT Usage - Lichy, Jessica; Merle, Karine (Management international / International Management / Gestiòn Internacional, 2020)
This study draws from concepts of socio-technical interaction to examine cross-cultural perceptions and usage of information and communication technologies (ICT). Set in the context of Continuing Professional Development (CPD) specialising in business skills, data were collected at two separate intervals in France and the UK, to observe the adoption of innovation over time in each cultural setting. The findings reflect ICT evolution and convergence, evidencing how users perceive and interact with ICT with different intensity and for different motives. Managerial implications were developed in response to the way in which ICT is shaped by the professional context in each country.